Optimization of Patrols by the Samapta Unit of the Demak Police Resort in Preventing Theft with Violence - Uluputty, Hasan Cahyadi (Advances in Police Science Research Journal, 2024)
The crime of theft with violence still dominates the list of most frequent criminal offenses in the jurisdiction of the Demak Police Resort. The Samapta Unit of the Demak Police Resort plays a crucial role in controlling and preventing these cases through preventive efforts such as patrols. Although the patrols are carried out regularly and efficiently, they are not yet optimal, as evidenced by the increasing number of theft cases in the jurisdiction of the Demak Police Resort in the last three years. This motivated the author to conduct further research on the optimization of patrols by the Samapta Unit of the Demak Police Resort in preventing theft with violence. This research employs a qualitative research approach with a case study design, where the author directly immerses themselves in the field as the research subject. Data collection techniques include observation, interviews, and documentation study through documents, and the data obtained is validated through triangulation as well as through data reduction, data display, and conclusion drawing. The research findings are then analyzed using the theories of Management Process, Management Elements, and SWOT. In the end, the author successfully identified the problem and found a solution through the symptoms that occurred, which was the consistency of patrols evaluated based on the Chief Regulation of the Security and Maintenance Agency and the Indonesian National Police No. 1 of 2017 regarding Patrols. Patrol is one of the effective preventive efforts in terms of process, but the optimal results have not been achieved sustainably. This is influenced by internal and external factors of the Indonesian National Police.